Developing Prosocial Behavior Of Early Children: Learning From “Adit & Sopo Jarwo” - M. Agung Hidayatulloh (STAI Miftahul Ula Nganjuk, 2018)
This article explored the description of prosocial behavior inserted in the film of “Adit and Sopo Jarwo” which can be taught to early children. The data was collected by documentation. This descriptive qualitative research analyzed five episodes of the selected film. Those episodes were taken from Season 1 and Season 2. The results showed that “playing with playmates” found in the 3rd film, “caring about others” found in all fims, “sharing (good and/or bad) experiences” found in the 4th film, “cooperative with others” found in the 1st until the 4th film, while “considering others (tolerance)” found in the 1st and the 3rd films. Further, “borrowing and lending out something to others” found in film 3, “showing enthusiasm” found in all films except film 4, “obeying the games/the rules” found in film 3, and “appreciative to others” found in film 1, 3, and 5. All of those prosocial behaviors can be taught to early children.